The Influence of Marketing Mix on Purchasing Decisions on E-Commerce Live Streaming Platforms - Verina, Rizky Nanda; Nurrachmi, Rininta; Zaerofi, Afif (Darul Yasin Al Sys, 2024)
This study aims to examine the influence of marketing mix (product, price, promotion, people, and process on purchasing decisions on E-commerce Live streaming platforms such as Shopee Live and Tiktok Live. The population of this study is consumers in Indonesia who have shopped through Live streaming commerce. The type of research used is quantitative research. Data analysis techniques using Structural Equation Modeling (SEM) and data processing using Partial Least Square (PLS) analysis with Smart PLS 3.2.9 applications. The research sample was 252 respondents, data were obtained using questionnaires with a Likert scale of 1-6. The results showed that price, promotion and people had a positive and significant effect on purchasing decisions. While products and processes do not have a significant effect on purchasing decisions in live streaming commerce.